STRENGTHENING BUSINESS PERFORMANCE BASED ON BUSINESS OPPORTUNITIES AND UNIQUE CAPABILITIES THROUGH BUSINESS STRATEGIES IN THE CREATIVE ECONOMIC INDUSTRY IN WEST JAVA DURING THE COVID- 19 PANDEMIC - Hermina, Nurul; Baskoro, Barry; Muharriansyah, Rizal Muhamad (CENTRAL ASIA AND THE CAUCASUS, 2022)
Creative industry plays an important role in economic development in Indonesia, especially in West Java. The creative industry is also believed to have strong enough resilience in the face of the COVID-19 pandemic. However, various strategies are needed so that the creative economy can still grow and develop in West Java. One of the efforts that can be made to encourage the creative industry in West Java to grow is to develop an appropriate business strategy based on business opportunities and unique capabilities. Through improvements to the business strategy, it is expected to be able to improve the business performance of the creative industry. The results of the analysis using the structural equation modeling method through partial least square path modeling found that business opportunities and unique capabilities make a significant contribution to business strategy and have a significant indirect impact on improving the performance of creative industries in West Java.